PENERAPAN SANKSI TERHADAP PENGGUNA TELEPON GENGGAM SAAT BERKENDARA - Dwi Syahputra (Fakultas Hukum Universitas Tulang Bawang, 2021)
The main focus of the research is the application of criminal sanctions against phone cell users while driving. The inhibiting factors in the application of criminal sanctions against cell phone users while driving. The approach method used in this research is normative and empirical with descriptive-analytical. The results showed that the application of sanctions against the use of mobile phones while driving by motorized vehicle drivers was directly given a proof of violation and after that it was continued with a trial process in court and then paid a fine according to the judge's decision. The inhibiting factor in the application of criminal sanctions against the use of cell phones while driving lies in community factors and cultural factors. Community factors are very influencing because the applied legal rules will not run well if human resources or the community itself are not aware of the importance of obeying traffic rules.